Cryopyrin-associated periodic fever syndrome manifesting as Tolosa-Hunt syndrome. (December 2016) - Höhne, C; Schuh, E; Kümpfel, T; Straube, A
Background: Tolosa-Hunt syndrome (THS) is characterized by unilateral orbital pain, ipsilateral oculomotor paresis and a prompt response to treatment with corticosteroids. Several reports have demonstrated that the clinical features of THS are not specific to one causal aetiology and can lead to misdiagnosis. Case report: We report the case of a patient diagnosed with THS after an episode of unilateral orbital pain and diplopia with demonstration of granulomatous inflammation of both cavernous sinus on cerebral magnetic resonance imaging and an immediate response to treatment with corticosteroids. Progression of the disease over the following years, accompanied by increasing signs of inflammation on cerebral magnetic resonance imaging and cerebrospinal fluid pleocytosis, led to further diagnostic tests. Genetic analyses revealed a heterozygote low-penetrance mutation (Q703K) of the cryopyrin/ NLRP3 gene compatible with a cryopyrin-associated periodic fever syndrome. Discussion: This case report demonstrates that THS can be a central nervous system manifestation of cryopyrin-associated periodic fever syndrome, which therefore represents a differential diagnosis of THS, even in elderly patients.